Study of Students’ Difficulties in Structure and Written Expression on Paper-Based TOEFL - Faishol Hadi (STKIP AL HIKMAH SURABAYA, 2020)
The aims of this study is to investigate student’ difficulties in Structure and Written Expression on Paper-Based TOEFL. The subjects of this study were ten students of English Department STKIP Al Hikmah Surabaya. This study used qualitative research method. The researcher used TOEFL test and interview in collecting the data. The study found the most students’ errors were from five item of TOEFL test, they were invert subject and verb. Multi clauses, reduced clause, form of the verb, and adjective and verb. This research also showed that the main factor causing students’ difficulty in TOEFL was lack of grammar.